2020
DOI: 10.1007/s10643-020-01080-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Diversity in Children’s Books in the Netherlands

Abstract: The present study examined the representation of authors, illustrators, and characters of color in books for young children (6 years old and under) that (1) have won awards, (2) were purchased most often, and (3) were borrowed most often from libraries in the Netherlands from 2009 to 2018. Factors influencing the prominence of characters were explored. In total, 64 books and 2053 characters were coded, and representation statistics were compared to statistics of the national population. Results suggest a sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Authors and illustrators are usually better able to represent the uniqueness and universality of the images of their own cultural group in books (Bista 2012;Youngs 2015). Previous studies have indicated that 88 to 96% of books for young children in Canada, the Netherlands, and the United States were written by White authors, and 83 to 94% books were illustrated by White illustrators (de Bruijn et al 2020;Dionne 2014;Eisenberg 2002;Garner and Parker 2018;Koss 2015;Koss et al 2017;Kurz 2012). Clearly, we see White dominance in terms of authors and illustrators among children's books.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Authors and illustrators are usually better able to represent the uniqueness and universality of the images of their own cultural group in books (Bista 2012;Youngs 2015). Previous studies have indicated that 88 to 96% of books for young children in Canada, the Netherlands, and the United States were written by White authors, and 83 to 94% books were illustrated by White illustrators (de Bruijn et al 2020;Dionne 2014;Eisenberg 2002;Garner and Parker 2018;Koss 2015;Koss et al 2017;Kurz 2012). Clearly, we see White dominance in terms of authors and illustrators among children's books.…”
Section: Introductionmentioning
confidence: 75%
“…In addition, illustrations of human characters in books may transmit physical feature preferences to children, impacting children's body image development and self-evaluation (Thompson and Heinberg 1999). White dominance in characters and authors in books for young children has been widely found in countries with majority White populations (e.g., de Bruijn et al 2020;Koss 2015;Koss et al 2017), suggesting fewer identification opportunities for underrepresented ethnic groups, as well as potential White-normative messages about physical appearance (Russell et al 1992). Given the highly developed globalized market and a history of White dominance in many parts of the world in (post-)colonial times, similar patterns might be present in children's books in other parts of the world where the majority of the population is not White.…”
Section: Introductionmentioning
confidence: 99%
“…The different representation of ethnic minorities allows the educator to discuss with their students how the experiences of grey versus color (Kenny lives with Erica and Martina) and the different color families (Goldilocks and the Five Bear Families) tie into current society. For students who are discriminated against due to their skin color, the presence of ethnic diversity in these books can provide important mirror and window connections, thereby fostering academic engagement (Maestri, 2016;Bruijn et al, 2020) and a sense of belonging (Youngs, 2015;Nishina et al, 2019).…”
Section: Diversitymentioning
confidence: 99%
“…In addition, one outlier regarding the number of human characters (estimated at 3343) was excluded. 1 The remaining books were firstly coded quantitatively (for the complete quantitative coding process, see de Bruijn et al 2021), after which the selection process for the qualitative analysis continued.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Scholars have advocated for the representation of ethnically diverse characters, so that all children can identify with characters and learn about other cultures. Various studies have established that characters of color in children's books are rare or underrepresented (e.g., de Bruijn et al 2021;Koss 2015;Koss et al 2017). In addition, mere representation is not enough for readers to identify with characters, or for books to teach children about various cultures: it is also important how these characters of color and their environments are portrayed, and what values and messages are conveyed within the stories.…”
mentioning
confidence: 99%